Temporal variability of selected physico-chemical parameters and primary productivity in estuarine water of kuching - Liaw, Sze Chieng (Universiti Malaysia Sarawak, UNIMAS, 2012)
Remote sensing is an important technology for broad-scale aquatic related researches. Unlike in situ methods, satellite data can provide synoptic data for a large study area. This study describes the results of temporal changes of chlorophyll a, temperature datasets and phytoplankton composition in estuarine waters as well as the validation of satellite chlorophyll a and temperature datasets with in situ datasets in estuarine Case 2 waters of Kuching for seven months. This study was carried out in Samariang and Santubong estuaries from 21st September 2011 until 2nd April 2012. The physico-chemical water parameters, phytoplankton abundance and composition, chlorophyll a (Chl-a) concentration and Total Suspended Solids (TSS) were studied. Based on the study, the in situ chlorophyll a mean concentration was 2.30±1.84 mg/m3 for Samariang estuary and 2.35±1.19 mg/m3 for Santubong estuary. There was no validation possible in Samariang and Santubong estuaries as the satellite instrument errors were too high. While for Bako estuary, the satellite derived Chl-a datasets were significant different with the in situ datasets on 16th November 2011 (r2 = 0.8602) but not significant different on 19th November 2011 (r2 = 0.2239). This study concludes that the accuracy of satellite derived Chl-a datasets to validate in situ datasets was depending on the water turbidity. There are limitations to validation during this study of which data of nearby overhead passes were often not available due to land masking, cloud cover and large errors near coastal waters.